Testing Software and Systems : 27th IFIP WG 6.1 International Conference, ICTSS 2015, Sharjah and Dubai, United Arab Emirates, November 23-25, 2015, Proceedings - El-Fakih, Khaled; Barlas, Gerassimos; Yevtushenko, Nina.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 27th IFIP WG 6.1 International Conference on Testing Software and Systems, ICTSS 2015, held in Sharjah and Dubai, United Arab Emirates, in November 2015. The 14 revised full papers and 4 short papers presented were carefully reviewed and selected from 42 submissions. The papers are organized in topical sections on model based testing, test derivation methods, monitoring and fault localization, model and system testing, and real-time systems.
Keywords: Software engineering; Computer Communication Networks; Computer science; Logic design; Information Systems; Software Engineering; Computer Communication Networks; Programming Languages, Compilers, Interpreters; Special Purpose and Application-Based Systems; Logics and Meanings of Programs; Management of Computing and Information Systems